Information Receiving Behavior of Farmers: The Structural and Functional Analysis (Indian Journal of Extension Education, 2023)
Farmers are the primary producers of food and other agricultural goods play a crucial part in the agricultural sector. Farmers need fast and accurate information on a variety of farming-related issues including weather, markets, pests and diseases, farming techniques, and agricultural inputs, to make informed decisions. Farmers’ information-seeking behaviour, however, differs based on several conditions. The proficiency in information-receiving behavior and its interpretation merit humongous importance for the triumph of entrepreneurial success far beyond subsistence farming. The study was conducted in the Nayagarh district of Odisha by selecting one hundred FPO member farmers following multistage and snowballing sampling techniques. A structured interview schedule was prepared and data were collected using the personal interview method. The study envisages that variables viz. age, crop yield, no. of male workers, marketed surplus, and materials possessed and training exposure have significant contributions to the functional contribution of information receiving behaviour of the farmers. The study suggests that improvement of farmers’ network and extension agent farmers’ relationship may be helpful for quick technology dissemination and overall improvement of the farming community.